Prototipe Sistem Pompa Air Tenaga Surya dengan Monitoring Tegangan Berbasis Internet of Things (IoT) - Alfan Habibillah; Alfian Ma'arif (Buletin Ilmiah Sarjana Teknik Elektro, 2021)
Several types of alternative energy are geothermal, biogas, wind energy, micro hydro and solar energy. Among these alternative energies, solar energy is the most potential energy to be utilized in Indonesia. A solar energy water pump system with a battery is a water pump that utilizes solar energy into electrical energy that is stored in batteries. The energy in the solar panels is stored in the battery as a source of electrical energy to pump water through the solar charge controller. In this study, monitoring the pump battery voltage remotely, monitoring using the Internet of Things (IoT) method by displaying it on the thingspeak website. The solar panel has a power of 10 Watts. Testing on the whole tool using panels and without using panels there are differences from these experiments. With a time of 10 minutes the initial voltage of the experiment using the panel is 13.24V and the final voltage is 11.90V, consuming 1.34V. Experiments without using a panel with a starting voltage of 12.09V and a final voltage of 10.48V, consuming 1.61V. In both experiments there is a difference of 0.27V, in the test using the panel charging occurs, so that it takes longer to reduce the power to the battery. Beberapa jenis energi alternatif adalah panas bumi, biogas, energi angin, mikro hidro dan energi surya. Di antara energi alternatif tersebut, energi matahari merupakan energi yang paling potensial untuk dimanfaatkan di Indonesia. Sistem pompa air energi surya dengan baterai adalah pompa air yang memanfaatkan energi matahari menjadi energi listrik yang disimpan di baterai. Energi pada panel surya di simpan ke baterai sebagai sumber energi listrik untuk pompa air melalui solar charge controller. Pada penelitian ini memantau tegangan baterai pompa dari jarak jauh, pemantauan menggunakan metode Internet of Things (IoT) dengan menampilkan pada website thingspeak. Panel surya memiliki daya sebesar 10 Watt. Pengujian pada alat keseluruhan dengan menggunakan panel dan tanpa menggunakan panel terdapat perbedaan dari percobaan tersebut. Dengan waktu 10 menit tegangan awal percobaan menggunakan panel 13,24V dan tegangan akhir 11,90V, menghabiskan sebanyak 1,34V. Percobaan tanpa menggunakan panel tegangan awal 12,09V dan tegangan akhir 10,48V, menghabiskan sebanyak 1,61V. Pada kedua percobaan tersebut terdapat selisih 0,27V, pada pengujian menggunakan panel terjadi pengisian daya, sehingga lebih lama pengurangan daya pada baterai.